Research on rule of law system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area - Ke Zhang; Er-He Chen; Yu-Lin Chen; Jun-Jie Li; Tao Huang; Wei Liu; Si-Hao Wei; Yu-Kang Tu (Frontiers in Marine Science, 2026)
The development of a legal system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area is a critical issue for cross-border ecological governance under the unique context of "One Country, Two Systems, Three Jurisdictions." This issue directly affects regional ecological security and the high-quality development of the marine economy. This paper uses comparative law and empirical analysis to systematically review the institutional frameworks and current practices of the three regions across four dimensions: Legislation, law enforcement, judicial adjudication, and legal regulation of public participation. The study finds that the current system faces core difficulties, including a disconnect in legislative coordination mechanisms, insufficient effectiveness in joint law enforcement, uncoordinated judicial collaboration, and insufficient legal safeguards for public participation. The root causes lie in the differences between regional legal systems, the absence of coordination mechanisms, poor resource integration, and fragmented participation channels. Based on this, the paper proposes a comprehensive improvement path. At the legislative level, we should establish a normalized coordination mechanism to promote the alignment of rules and standards. At the enforcement level, we should build a unified coordination platform to deepen cross-border collaboration and resource sharing. At the judicial level, we should improve cross-border collaboration norms and improve mechanisms for identifying and repairing ecological damage. At the level of public participation, we should build a unified cross-border platform to strengthen collaborative systems and public interest cooperation. The research aims to provide a governance model for regional marine environmental protection under "One Country, Two Systems, Three Jurisdictions," offering theoretical support and practical guidance for solving cross-border ecological governance problems, and assisting in the construction of a strong maritime nation and the improvement of the global marine governance system.